Efektivitas dan Efisiensi Pengelolaan Keuangan Dana Desa pada Dalu Sepuluh A Tanjung Morawa - Egy Aulia; Khairina Tambunan; Nur Laila (Penerbit Goodwood, 2024)
Purpose: To evaluate the effectiveness and efficiency of financial management of village funds in Dalu Sepuluh A Village, Tanjung Morawa. Research Methodology: Comparative analysis using effectiveness and efficiency formulas. Document analysis of financial reports and budget plans. Interviews with village officials. Results: Village fund budget management in Dalu Sepuluh A Village did not meet efficiency standards. The effectiveness ratio is 100%. Improvements include better budget planning and increased transparency in financial reporting. Limitations: The study focused on a single village for one fiscal year, limiting its generalizability. Reliance on self-reported data from village officials. Contribution: The findings will contribute to local government financial management, rural development studies, and public administration. This study provides insights for policymakers on village fund management in Indonesia.